2015
DOI: 10.1002/adfm.201501120
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance Nitro‐Explosives Schottky Sensor Boosted by Interface Modulation

Abstract: 4039wileyonlinelibrary.com mole cules and depends highly on the analyte concentrations. [8][9][10][11][12] As a result, the traditional Ohm-contacted nanosensor has diffi culty in realizing the ultrasensitive detection in real circumstances where open environment must be considered. Recently, it was demonstrated that Schottky contact could largely improve the sensitivity of nanosensors due to that Schottky barrier serves as a "gate" controlling the current passing through the barrier, [ 13,14 ] and the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…The responses for PA and RDX are 36.1% and 45.5%, which are much higher than those of the best Schottky sensor based on SiNWs array/TiO 2 /rGO junction (4% for PA and 9% for RDX) . What is more, all the response time and recovery time for TNT, DNT, PA, PNT, and RDX are less than 8 s, which is remarkably superior than all of the other sensors . This comparison further confirms that the present transition‐metal‐doping method could be a very promising strategy to put the nanomaterials‐based explosive sensors into practical application.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The responses for PA and RDX are 36.1% and 45.5%, which are much higher than those of the best Schottky sensor based on SiNWs array/TiO 2 /rGO junction (4% for PA and 9% for RDX) . What is more, all the response time and recovery time for TNT, DNT, PA, PNT, and RDX are less than 8 s, which is remarkably superior than all of the other sensors . This comparison further confirms that the present transition‐metal‐doping method could be a very promising strategy to put the nanomaterials‐based explosive sensors into practical application.…”
Section: Resultssupporting
confidence: 65%
“…The comparison of the performance (including the sensor response, response time, and recovery time) of the present transition‐metal‐doped ZnO nanoparticle‐based sensors and other recently reported chemiresistor or Schottky sensors toward explosive vapors detection can be found in Table 1 . It is clearly shown that the present transition‐metal‐doped ZnO nanoparticle‐based sensors belong to the best TNT and DNT sensors since the responses toward them are 45.5% and 38.9%, respectively, and are comparable to the best titania (B) nanowires‐based chemiresistor gas sensor (47% for TNT and 38% for DNT). The responses for PA and RDX are 36.1% and 45.5%, which are much higher than those of the best Schottky sensor based on SiNWs array/TiO 2 /rGO junction (4% for PA and 9% for RDX) .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…For metal-oxide nanomaterials, because the high surface-to-volume ratio and surface defect of nanostructures, which made the metal-oxide nanomaterials are quite sensitive for the environment variation [19][20][21][22][23][24][25][26] . Many articles reported that Schottky contact mechanism can enhance the performance of metal-oxide nanomaterials, such as piezotronic devices 27,28 , nanogenerators [29][30][31][32] and nanosensors 20,[33][34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Explosives detection‐related terrorist attack has become a major threat to the homeland security and social stability, and thus the exploration of reliable detection methods toward trace explosives is of great urgency . Up to now, much efforts have been made in the field of trace explosives detection, such as ion mobility spectrometry method, fluorescent method, and gas sensing method . Among them, the detection of vapor‐phase explosives has the merits of noncontacting and simple sampling.…”
mentioning
confidence: 99%